Pemantauan Logam Berat pada Histologi Ikan Badukang (Arius Caelatus Valenciennes 1840) Muara Sungai Kahayan dan Katingan, Kalimantan Tengah - Edison Harteman (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
The study was conducted of Kahayan and Katingan estuary, Central Kalimantan. The research aim was to evaluate the distribution of heavy metals contaminated in histological of liver, kidney, gills, muscle and skin of Catfish (Arius caelatus Valenciennnes 1840). Catfish organ samples were taken in July, Augustus, September and October 2012. Detection of heavy metals in histological of catfish was done using dye hematoxyline. Treatments of fish organ samples were using the histotechniques method. The results showed that the liver, kidney, gills, skin and muscle of fish were detected to contaminated Al, Cr, Fe, Ga, Hf, In, Zr (blue-black); Be, Dy Ho, Ir, Mn, Mo, Nd, Ni, Pb, Pt , Rh, Tb, U, Zn (Blue), Nb and Ti (Brown) with clustered and random distribution patterns. Metals accumulation in liver, kidney and gill were detected much heavier than in the muscle.